Bilingual parsing strategies in Basque and Spanish - Leeser, Michael J.; Prieta, Raquel (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2015)
Over the last several years, one area of sentence processing research that has received considerable attention is how native speakers resolve structural ambiguities while reading, as in Someone shot the servant of the actress who was on the balcony (e.g., Cuetos & Mitchell 1988). Cross-linguistic research on this kind of ambiguous relative clause (RC) attachment has revealed that speakers of some languages prefer to attach the RC who was on the balcony to the first noun phrase (the servant), whereas speakers of other languages prefer attachment to the second noun phrase (the actress). From the perspective of bilingual sentence processing, research on RC attachment can provide insight into a number of important issues related to language transfer, language attrition, and processing efficiency. The present study, therefore, seeks to build upon some of these lines of research by examining the on-line parsing strategies among native speakers of Basque (N = 17) on two self-paced reading tasks in Basque and Spanish. Our purpose was to investigate which parsing routines these bilinguals utilized for each language in order to determine whether they maintained separate strategies or adopted one strategy for both languages. Analyses of reading times at critical regions in experimental sentences suggest that this group of bilinguals employed a single parsing strategy in Basque and Spanish. The findings are discussed within recent proposals of monolingual and bilingual sentence processing.